Intensitas Nyeri Persalinan Kala I Fase Laten pada Ibu Inpartu menggunakan Birth Ball Exercise - Putu Indah Sintya Dewi; Kadek Yudi Aryawan; Putu Agus Ariana; Ni Ayu Putu Eka Nandarini (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to analyze the effect of birth ball exercise on the intensity of labor in the first stage of latent phase in mothers of mothers in BPM "LM" Desa Giri Emas. The method used in this study uses a one group pre-post test design. The results obtained p value (0.007) <Î± (0.05. Conclusion: it was concluded that there was an effect of birth ball exercise on the intensity of labor pain in the first stage of latent phase for mothers in the mother in BPM "LM" Desa Giri Emas. Keywords: Birth Ball Exercise, Pain Intensity, Childbirth, First Stage Latent Phase